Geosynthetics Materials: Recent Advancements for ground Improvements. - Kumar, Tarun (IJRDO-Journal of Applied Science, 2015)
Geosynthetics are man-made materials used to improve Ground conditions.. The material properties of geosynthetics are important to their use in various applications like canal lining, used for increasing bearing capacity and permeability of soil, reducing settlement of soil, soil reinforcement, soil stabilization etc.Geosynthetics have become well established construction materials for geotechnical and environmental applications in most parts of the world. This paper focuses on recent advances on geosynthetics products, applications and design methodologies required for reinforcing soil, ground improvement and environmental protection work.